2008
DOI: 10.1063/1.3006443
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight mobility measurements in organic field-effect transistors

Abstract: We implement the “time-of-flight” (TOF) method for charge carrier mobility (μ) measurements in organic field-effect transistors (OFETs) by applying voltage steps, VS, to OFETs. We use the electric scheme for OFET-TOF introduced by Dunn et al. [Appl. Phys. Lett. 88, 063507 (2006)]. Our investigation of a series of low-threshold poly(triaryl amine) OFETs with different channel lengths, L, suggests that in the OFET-TOF setup, the effective voltage driving carriers across the channel, VTOF, is reduced from VS by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…A discussion of the appropriate timescales and the justification of this assumption is given in the supplementary information (SI Section §2.1). This mobility calculation is more similar to time-of-flight experiments, where low excitation fluence, charge density, and active layer thickness are required [132,133], than field-effect transistor measurements on complete devices, which tend to report mobilities several orders of magnitude greater [134][135][136]. Figure 9.…”
Section: Charge Mobilitymentioning
confidence: 71%
“…A discussion of the appropriate timescales and the justification of this assumption is given in the supplementary information (SI Section §2.1). This mobility calculation is more similar to time-of-flight experiments, where low excitation fluence, charge density, and active layer thickness are required [132,133], than field-effect transistor measurements on complete devices, which tend to report mobilities several orders of magnitude greater [134][135][136]. Figure 9.…”
Section: Charge Mobilitymentioning
confidence: 71%
“…GV D curves are more complex, but similar in shape to the transients observed when OFETs are driven with external, rectangular V S pulses. 8,9 We clearly observe V S switching between Ϯ3 V when GV D crosses V ref = 1.4 V. We explain the asymmetric duty cycle by the faster switching of the OFET from on to off, than vice versa, because traps in the channel are filled when the OFET is on and hence, mobility is higher. We have made similar observations when OFETs were driven with external V S pulses.…”
Section: ͑1͒mentioning
confidence: 86%
“…We have made similar observations when OFETs were driven with external V S pulses. 8 The nonperfect flanks indicate that the comparator's switching time is not negligible, despite the timescale in Fig. 2 being rather slow ͑10 ms/division͒.…”
Section: ͑1͒mentioning
confidence: 98%
“…It is assumed only that carrier transport is described as the drift in the average electric field V ds =L at a constant velocity v ¼ V ds =L. Later TOF study of Dost et al 13) suggested using the drain-source voltage reduced by the threshold (V ds À V th ) instead of V ds . This result was supported by the experiment, even though the detail explanation was not clear.…”
Section: Introductionmentioning
confidence: 99%